Magnetic resonance imaging manifestations of cerebral small vessel disease: automated quantification and clinical application - Lei Zhao; Allan Lee; Yu-Hua Fan; Vincent C.T. Mok; Lin Shi; Yan-Jie Yin; Xiu-Yuan Hao (Chinese Medical Journal, 2021)
Abstract. The common cerebral small vessel disease (CSVD) neuroimaging features visible on conventional structural magnetic resonance imaging include recent small subcortical infarcts, lacunes, white matter hyperintensities, perivascular spaces, microbleeds, and brain atrophy. The CSVD neuroimaging features have shared and distinct clinical consequences, and the automatic quantification methods for these features are increasingly used in research and clinical settings. This review article explores the recent progress in CSVD neuroimaging feature quantification and provides an overview of the clinical consequences of these CSVD features as well as the possibilities of using these features as endpoints in clinical trials. The added value of CSVD neuroimaging quantification is also discussed for researches focused on the mechanism of CSVD and the prognosis in subjects with CSVD.